The effect of irrigation regimes on plum (Prunus cerasifera) root system development dynamics. (4th July 2019) - Cochavi, Amnon; Rachmilevitch, Shimon; Bel, Golan
Abstract: Prunus genus species are widely spread in semi-arid regions due to their ability to adjust to the limited water supply. Former research described the effect of water deficit on their aboveground development. However, less is known about the effects of water stress on the development of the root system. In order to investigate the effects of the irrigation regime on the root system development, young plum ( Prunus cerasifera ) trees were grown under three irrigation regimes for a period of five months. The effects of the irrigation regime on different root order and total root system elongation, biomass growth and tip numbers were analyzed. The results indicate that the responses vary according to the stress level. Under moderate stress, the total root system biomass decreases relative to the full irrigation treatment. However, low-order root formation remains similar to that found under no stress conditions. Under severe stress, the formation of low-order roots is also inhibited. Our results suggest that plum trees' response to water deficit stress escalates according to the stress level. Namely, moderate stress affects the growth rate of the root system but does not alter the relative contribution of different orders, while severe stress both inhibits the total growth and changes the relative contribution of the different root orders. The combined measurements of the total root system and the different orders enable the identification of a stepwise response to water stress.